ESTUDIOS SOBRE LOS LIPOIDES DE LAS CELULAS NERVIOSAS II RELACIONES CON EL APARATO DE GOLGI - NIETO, DIONISIO; ESCOBAR, ALFONSO I (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1949)
A cytological study of the bone marrow of rabbits was made following supravital staining with neutral red and Janus green In the process of evolution the chondrioconts undergo a physical change becoming lengthened and then fragmented into granulations A
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, LIPOIDES, CELULAS, NERVIOSAS, RELACIONES, APARATO- GOLGI; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA